2021
DOI: 10.2147/ijgm.s328222
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analyses Reveal the Prognostic Value and Biological Roles of SEPHS2 in Various Cancers

Abstract: Purpose Selenophosphate synthetase 2 (SEPHS2) has been shown to regulate selenoprotein biosynthesis by catalyzing the synthesis of active selenium donor selenophosphate. SEPHS2 influences the survival of tumor cells. However, few studies have explored the expression level and prognostic of SEPHS2 in various cancers. Methods The expression of SEPHS2 in human tumor tissues and normal adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The current GBM prognosis is abysmal, with a median survival time of 12-15 months under standard treatments [24]. Recent evidence from clinical trials showed that targeted therapy does not improve the prognosis of patients with GBM [25]. TMB has been reported to influence immunotherapeutic effectiveness across tumor types and can be used to predict the survival of diverse tumors with CTLA-4 or anti-PD-1 treatments [26].…”
Section: Discussionmentioning
confidence: 99%
“…The current GBM prognosis is abysmal, with a median survival time of 12-15 months under standard treatments [24]. Recent evidence from clinical trials showed that targeted therapy does not improve the prognosis of patients with GBM [25]. TMB has been reported to influence immunotherapeutic effectiveness across tumor types and can be used to predict the survival of diverse tumors with CTLA-4 or anti-PD-1 treatments [26].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the role of SEPHS2 is to provide the active Se donor, and SPS1 does not have a clear function established, but it could have a non-essential role in selenoprotein metabolism [204]. SEPHS2 is related to the aggressiveness and malignant tumor grade [205,206]. Its expression is related to immune infiltration, and it could act in the development of tumors through the peroxisome proliferator-activated receptors signaling pathway [205].…”
Section: Selenophosphate Synthetasementioning
confidence: 99%
“…SEPHS2 is related to the aggressiveness and malignant tumor grade [205,206]. Its expression is related to immune infiltration, and it could act in the development of tumors through the peroxisome proliferator-activated receptors signaling pathway [205].…”
Section: Selenophosphate Synthetasementioning
confidence: 99%
“…Se supplementation has been shown to lessen the occurrence and severity of carcinogenesis in the liver, esophagus, pancreas, prostate, colon, and mammary glands [11]. In patients with glioblastoma, se therapy reduced tumor severity and relieving disease manifestations [12]. The antioxidant enzyme GPX1, was the rst discovered mammalian selenoprotein in GPXs, which is commonly found in cell mitochondria and cytoplasm, has been linked to tumor spread and transformation in tumor cells [13,14].…”
Section: Introductionmentioning
confidence: 99%